THE FIRST WORLD WAR AS DEPICTED IN HISTORY TEXTBOOKS (ARGENTINA, BRAZIL, CHILE, MEXICO, AND THE UNITED KINGDOM) / A PRIMEIRA GUERRA MUNDIAL NA ESCRITA DE LIVROS DIDÁTICOS DE HISTÓRIA (ARGENTINA, BRASIL, CHILE, MÉXICO E REINO UNIDO) - Justino (Brasil), Rogério; Gatti Júnior (Brasil), Décio (Revista História da Educação, 2017)
This paper communicates the results of research in the area of the History of School Subjects, the object of which is the way the theme of the First World War has been depicted in textbooks used in Brazil and abroad.  A premise of this study is that textbooks are important tools in school life, contributing to the vision students have of the world. As such, five different textbooks used in Argentina, Brazil, Chile, Mexico, and the United Kingdom were analyzed.  It was observed that there was predominance of a narrative based on the explanatory triad – antecedents, development, and consequences; emphasis on an androcentric discourse, backed up with great names and deeds, with a Eurocentric bias; and dissonance in the interpretations made in the books analyzed, and only in the British book did the conflict occur as a result of an accident.